TINJAUAN HUKUM TERHADAP PERCERAIAN AKIBAT PERESELINGKUHAN (Studi Putusan Nomor : 0032/Pdt.G/2015/PA.Msa) - Rasdianah Rasdianah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
This experiment aims to: (1) to determine whether the affair could serve as a reason for divorce, (2) to find out the considerations in the judge granted the request divorce due to infidelity. Verdict number: 0032/Pdt.G/2015/Pa.Msa. This study using the research type normative empiricial the fokus research on secondary data sources and supported by primary data the research literature and research directly in the field, in the form of direct interviews in the field, with the relevant parties to discuss the issues to be discussed in this thesis. The results of this study showed : (1). that divorce due to infidelity in decision numbers : 0032/Pdt.G/Pa.Msa in terms of Law No. 1 of 1974 concerning marriage and compilation of Islamic law when the marriage broke up because of divorce, “to divorce there must be a reason,” if the husband and wife can not live peacefully as husband and wife